Metabolomic and Confocal Laser Scanning Microscopy (CLSM) Analyses Reveal the Important Function of Flavonoids in Amygdalus pedunculata Pall Leaves With Temporal Changes - He, Yueyue; Pan, Lei; Yang, Tao; Wang, Wei; Li, Cong; Chen, Bang; Shen, Yehua (Frontiers in Plant Science, 2021)
Amygdalus pedunculata Pall (Rosaceae, Prunus, Prunus pedunculata (Pall.) Maxim.) belongs to the Rosaceae family and is resistant to cold and drought. Ultra-performance liquid chromatography quadrupole time-of-flight mass spectrometry and metabolomics were used to track the changes in bioactive metabolites during several stages of Amygdalus pedunculata Pall growth. A total of 827 different metabolites were detected, including 169 flavonoids, 68 organic acids, 35 terpenoids and 2 tannins. Flavonoid biosynthesis and flavone and flavonol biosynthesis were the main synthetic sources of flavonoids. 3 biomarkers related to growth and development were found. Among them, quercetin, which connects the biosynthesis of flavonoids and the biosynthesis of flavones and flavonols, is very important for the synthesis of flavonoids in their leaves. The contents of isoquercitrin and epicatechin increased uniformly during the whole growth process from the flowering stage to the fruit ripening stage, indicating that these compounds play key roles in the growth and fruiting stages of their. The tissue location and quantitative analysis of flavonoids in leaves at different stages were performed by confocal laser scanning microscopy. The flavonoids were mainly distributed in the palisade tissue and spongy tissue, indicating the need for protection of these sensitive tissues in particular. Through comprehensive and systematic analysis, the temporal distribution of flavonoids in the process of their leaves growth was determined. These results clarify the important role of flavonoids in the developmental process of Amygdalus pedunculata Pall.